2015
DOI: 10.3389/fnagi.2015.00104
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal deferoxamine attenuates synapse loss via up-regulating the P38/HIF-1α pathway on the brain of APP/PS1 transgenic mice

Abstract: The widely recognized neuroprotective effect of iron chelators is contributed by their ability to prevent reactive oxygen species (ROS) generation via the Fenton reaction, which sequesters redox-active Fe. An additional neuroprotective mechanism of iron-chelating compounds is to regulate the transcriptional activator hypoxia-inducible factor 1α (HIF-1α). In the present study, we observed that intranasal administration of deferoxamine decreased beta-amyloid (Aβ) deposition and rescued synapse loss in the brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 56 publications
5
59
1
Order By: Relevance
“…distribution of Fe and did not attenuate the total content of Fe in brains of APP/PS1 mice, Guo, et al, 2015. A similar result was observed in the Perl's DAB analysis of the present study.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…distribution of Fe and did not attenuate the total content of Fe in brains of APP/PS1 mice, Guo, et al, 2015. A similar result was observed in the Perl's DAB analysis of the present study.…”
supporting
confidence: 92%
“…However, the intranasal DFO treatment showed a marked induction of GAP43 protein levels, indicating that intranasal DFO treatment improved brain recovery. 14 We previously showed that intranasal DFO treatment had a positive effect on HIF-1α gene and protein expression, leading to the up-regulation of several target genes and potentially to neuroprotection in the APP/PS1 mouse brain (Guo, et al, 2015). …”
Section: Gfap a Major Component Of Intermediate Filaments In Astrocymentioning
confidence: 99%
See 3 more Smart Citations